Optimization of PCR Purification Using Silica-Coated Magnetic Beads - Berdimuratova, K.T.; Amirgazin, A.O; Kuibagarov, М.А.; Lutsay, V.B.; Mukanov, K.K.; Shevtsov, A.B. (Eurasian Journal of Applied Biotechnology, 2020)
Purification of nucleic acids is still an important step in molecular genetic research. The development of whole genome sequencing technologies has increased the requirements for the purity of the nucleic acids used, and also required the selection of DNA fragments by size. Buffer systems that contain PEG/NaCl solutions and silica-coated magnetic beads allow to purify nucleic acids and selectively sorb certain sizes of DNA. In this article, we present a simple protocol for the purification of PCR products with the ability to absorb the required DNA molecules. It was determined that the use of an optimized PEG / NaCl buffer system with magnetic silica gel in a ratio of 1.5: 1 with a PCR product allows to get rid of DNA fragments 100 and less base pairs (bp), as well as other contaminants, while maintaining this is more than 90% of the DNA in solution. The ratio of 0.35: 1 allows for high-affinity sorption of DNA molecules larger than 400 bp. The practical use of the obtained data allows us to improve the quality of sequencing without increasing the cost of research.